PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN GO-JEK DI SAMARINDA - Heriyanto, Slamet Maryanto 1, Eddy Soegiarto (EKONOMIA, 2020)
The purpose of this study was to determine and assess the magnitude of the simultaneous and partial influence of service quality (reliability, responsiveness, assurance, empathy and tangible) on customer satisfaction on GO-JEK in SamarindaTheory used regarding marketing management, service quality and customer satisfaction.This study uses quantitative data obtained from questionnaire data. The number of research samples is 100 people with the taking method using simple random sampling. The analysis tool uses multiple linear regression analysis using the F test and t test.From the results of the F test, the results show that the five variables of reliability, responsiveness, assurance, empathy and tangible have a simultaneous effect on customer satisfaction where the value of F count> F table so that the first hypothesis is accepted.Variable reliability has a low partial correlation effect on GO-JEK consumer satisfaction in Samarinda. Based on the t test (t test) it turns out that the independent variable reliability has a partial effect on customer satisfaction (t count> t table). So that the second hypothesis is accepted.customer satisfaction. Based on t test (t test) it turns out that the independent variable responsiveness has a partial effect on customer satisfaction (t count> t table). So that the third hypothesis is accepted.The assurance variable has a low partial correlation effect on customer satisfaction. Based on the t test (t test), it turns out that the independent assurance variable has a partial effect on customer satisfaction (t count> t table). So that the fourth hypothesis is accepted.Empathy variables have the effect of a strong partial correlation on customer satisfaction. Based on t test (t test) it turns out that the independent variable emphaty has a partial effect on customer satisfaction (t count> t table). So that the fifth hypothesis is accepted.Tangible variables have the effect of a strong partial correlation on customer satisfaction. Based on t test (t test) it turns out that the independent variable tangible has a partial effect on customer satisfaction (t count> t table). So that the sixth hypothesis is accepted